TINJAUAN WILAYAH KOMUNIKASI PADA PENGGUNAAN SHIJISHI KO-SO-A DALAM WAWANCARA INTERAKTIF BAHASA JEPANG - Irma Winingsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
Deixis are words meaning pointing. Accroding to Levinson (1983:54), deixis are classified into five types, they are person deixis, time deixis, place deixis, social deixis, and discourse deixis. This research is a descriptive qualitative one using sociopragmatic approach. The aim of this research is to describe the information in the use of shijishi ko-so-a. The method used in this research is participatory one using the theory of Kinsui (1989), Yuuji(1999) and Akio (1990). The source of data of this research is the interactive interview in University of Kyuushuu, Japan. The corpus of the data are in the form of clauses containing  shijishi ko-so-a. The result shows that shijishi so is the mostly used in the interactive interview because the setting is formal and the relationship between the speaker and hearer is equal. As the people that know each other for the first time , they have to respect each other and use polite language because in Japanese society, a new person is a meuenohito’ that is a person that must be respected more than us. The mostly used references are anaphoric ones because the topic is flexible. The hearer is the one who has the highest  information area because the speaker admits and respect the owner of information, that is the hearer.